Nutritional support and outcome in hospitalized dogs and cats - Carcioti, A. C.; Brunetto, M. A.; Sampaio Gomes, M. O.; André, M. R. (My University, 2006)
This study investigated the effect of assisted nutritional support on the outcome and time of hospitalization (TH) of dogs and cats. The study compared two groups of 400 hospitalized animals. The animals in group 1 did not receive assisted nutritional support because they were hospitalized before the clinical nutrition service was implemented; animals in group 2 were nutritionally managed. Animals in group 1 received a low-cost diet with no consumption control. Group 2 animals had their maintenance energy requirement (MER) calculated, received a high-protein and high-energy super-premium diet, had their caloric intake (CI) monitored, and received enteral and parenteral nutritional support when necessary. The statistical analysis of the results included the standard T test (group 1 versus group 2) and chisquare and Spearman's correlation to evaluate group 2 (CI and outcome, body condition score (BCS) and outcome, BCS and CI). For group 2, favorable outcome (FO), defined as the percent responding to therapy and dis-charged from the hospital, was 83%, and the TH was 8.59 days. These values were lower (P < .001) for group 1 (63.2% FO and TH of 5.7 days). For group 2, 65.5% of the animals received voluntary consumption (93.1% outcome), 14.5% received enterai support (67.9% FO), 6.5% received parenteral support (68% FO), and 6.17% did not eat (38.5% FO), demonstrating an association between the type of nutritional support and outcome (P < .01). Group 2 animals that received 0% to 33% of their MER had 62.9% FO, and those receiving more than 67% had 94.3% FO, which shows that lower mortality rates are associated with higher CI (P < .001). TH was higher for animals with higher CI (P < .001). The BCS did not correlate with Cl (P > .05) but did correlate with outcome (P < .01). FO was 68.7% for animals with low BCS, 85.7% for animals with ideal BCS, and 86.6% for overweight animals. Nutritional support could allow for longer therapies, thus increasing the TH and FO rate.
Keywords: Animalia; Canis familiaris